Long-term Survivorship and Failure Modes of Unicompartmental Knee Arthroplasty - Foran, Jared R. H. (Springer-Verlag, 2012)
BACKGROUND: In a previously reported series of 51 patients with 62 cemented, fixed-bearing unicompartmental knee arthroplasties, we reported a 10-year, 98% survival rate with an average knee score of 92 points. The survivorship and modes of failure past 10 years are incompletely understood. QUESTIONS/PURPOSES: At 15-year followup we sought to determine (1) the overall durability and survivorship of this design; (2) modes of failure; and (3) the progression of arthritis in the nonresurfaced compartments. METHODS: Nineteen knees in 16 patients were available for study with 34 patients lost to death and one lost to followup. At 15 years, we analyzed the Kaplan-Meier survivorship as well as durability with regard to radiographic loosening and knee scores, determined modes of failure, and assessed radiographs for degeneration in the nonresurfaced compartments. RESULTS: Fifteen-year survivorship was 93% and 20-year survivorship was 90%. Four of 62 knees were revised to total knee arthroplasty at a mean of 144 months. One knee was revised for patellofemoral and lateral compartment degeneration, one for lateral compartment degeneration, one for polyethylene disengagement and metallosis, and one for pain of unclear etiology. No patients had aseptic loosening or osteolysis. The mean knee score was 78 at latest followup. Arthritic progression in the nonresurfaced compartments was common although symptomatic in only two patients. CONCLUSIONS: With this cemented, fixed-bearing design, the failure rates were low, there were no cases of failure secondary to wear or loosening, and the survivorship was similar to that reported for total knee arthroplasty. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.